THE PREVALENCE OF BLOOD GLUCOSE AND BODY MASS INDEX IN ELDERLY PEOPLE AT PANTI WERDHA TRESNA IN GIANYAR BALI. (PRELIMINARY STUDY - Kaur, Jaspreet; Ni Made, Linawati (Bali Journal of Medical and Health Sciences; Vol 1 No 1 (2017): volume 1 no 1 Januari 2017, 2017)
Blood glucose also known as blood sugar is the amount of glucose that can be found in the blood. Carbohydrate foods are the main source of energy for the human body. The rise of blood glucose is usually at peak when the individual’s age reach around 50’s as the body function decreases which effects the glucose metabolism and also the elderly body weight. The purpose of this study is to know the prevalence of blood glucose and body mass index in elderly individual. The design of the study is descriptive cross-sectional study. This study was carried out at Panti Werdha Tresna which is located at Jln. Gumitir, Denpasar,Bali. The number of elderly individuals in that old folks house was around 40 which consist of both females and males. The age range was 53-80 years old. A day before the research was carried out the elderly individuals was given informed consent and was asked to fast for at least 8 hours before the blood sample was taken. The amount of blood withdrawn was about 2cc. The results showed that 1 person (4.8%) of male and 3 person (14.3%) of females are overweight while 2 person (9.5 %) females are obese. Total 6 elderly individual with BMI above normal range. For blood glucose more than 100 mg/dL, there are 3 person (60%) males and 12 person (75%) females. The prevalence of high blood glucose is higher in female (75%) compared with male (60%). Based on the results, it can be concluded that the number of samples that has high blood glucose and high BMI is only 2 person (13.3%) of the total samples. It is  suggested that the government could create a program that can reduce morbidity and mortality due to complications of high blood sugar in the elderly individuals. Keywords : blood glucose, body mass index, elderly.